Implications of Radical Constructivism Theory on Learning Strategies at Nurul Yaqin Junior High School in Pringsewu Lampung - Addzaky, Khoirul Umam; Mukhsin, Mukhsin (ARZUSIN, 2024)
This research aims to analyze the implication of radical constructivism theory on learning strategy in Nurul Yaqin Junior High School Pringsewu Lampung and its impact on students. The research method used is a case study at Nurul Yaqin Junior High School in Pringsewu Lampung with data collection techniques through in-depth interviews, observations, and document studies. Data analysis was conducted using interactive analysis from Miles and Huberman. While the validity of the data is done by triangulation technique. The results showed that the implementation of radical constructivism triggered a shift in student-centered learning strategies, such as project-based learning, problem-based learning, scientific inquiry, and collaborative learning. The implementation faces challenges related to teacher readiness, availability of infrastructure, classroom management, and resistance to change. However, positive impacts are starting to be seen such as increased student engagement, creativity, learning motivation, and critical thinking and problem-solving skills. It is concluded that a strong commitment from various parties is needed for the optimal implementation of radical constructivism in order to realize more meaningful learning and produce quality graduates.